2021
DOI: 10.1097/hjh.0000000000003049
|View full text |Cite
|
Sign up to set email alerts
|

Higher aldosterone is associated with increased renal impairment risk in patients with hypertension and abnormal glucose metabolism: a longitudinal study

Abstract: Objective: The aim of this study was to evaluate the association between plasma aldosterone concentration (PAC) and renal impairment in patients with both hypertension and abnormal glucose metabolism (AGM). Methods: The longitudinal observational study included 2033 hypertensive individuals with AGM who did not have chronic kidney disease (CKD) at baseline. CKD was defined as estimated glomerular filtration rate (eGFR) less than 60 ml/min per 1.73 m 2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 34 publications
0
11
0
Order By: Relevance
“…Participants were inpatients from Hypertension Center of People’s Hospital of Xinjiang Uygur Autonomous Region in this retrospective study. The study design have been reported elsewhere ( 17 , 18 ). In brief, a total of 2,946 participants aged ≥ 18 years who diagnosed with hypertension and abnormal glucose metabolism between January 2012 and May 2019, were identified.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Participants were inpatients from Hypertension Center of People’s Hospital of Xinjiang Uygur Autonomous Region in this retrospective study. The study design have been reported elsewhere ( 17 , 18 ). In brief, a total of 2,946 participants aged ≥ 18 years who diagnosed with hypertension and abnormal glucose metabolism between January 2012 and May 2019, were identified.…”
Section: Methodsmentioning
confidence: 99%
“…Diagnostic criteria for hypertension and abnormal glucose metabolism [including impaired fasting glucose (IFG), impaired glucose tolerance (IGT), and diagnosed DM] have been described in previous studies ( 17 , 18 ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Model 2 was adjusted for variables with significant differences among CVAI quartile groups, including age, sex, smoking status, drinking status, SBP, baseline eGFR, duration of hypertension, types of AGM, antidiabetic drugs, antihypertensive drugs, HbA1c, BUN, and hyperuricemia. Model 3 was adjusted for all included factors, including PAC, which has been recently shown to be independently associated with incident renal damage in hypertensives with AGM ( 20 ). Hazard ratios (HRs) for outcomes were calculated for quartiles CVAI (with the first quartile as reference), high CVAI (with the group below the median of CVAI as reference), and each SD increase of CVAI.…”
Section: Methodsmentioning
confidence: 99%
“… 17 In addition, results may be biased by insufficient adjustment for confounding factors, such as aldosterone, which has recently been shown to be independently associated with incident CKD in hypertensive patients with GMD. 18 Therefore, the independently predictive value of PRA for kidney damage needs further validation.…”
Section: Introductionmentioning
confidence: 99%